Bacurú Drõa: Indigenous forest custody as an effective climate change mitigation option. A case study from Darién, Panama - Kunz, Matthias; Barrios, Hector; Dan, Michelle; Dogirama, Iran; Gennaretti, Fabio; Guillemette, Mathieu; Koller, Alexandra; Madsen, Chris; Lana, Gilberto; Ortega, Alexis; Ortega, Manuel; Paripari, Jose; et al. (Frontiers in Climate, 2022)
As countries around the world develop their climate mitigation strategies, the importance of engaging the forest sector is ever more pressing. Efforts to naturally remove atmospheric CO2 demand that permanent, largely intact forests be maintained because they can respond to environmental stressors in an adaptive way. Storing over half of terrestrial carbon, tropical forests are at the forefront of climate action. We present the results of an inter-cultural research initiative testing the hypothesis that Indigenous custody of the land is compatible with the maintenance of intact forests in Panama’s Darién. These forests are the core of the largest intact primary forest in Central America. Using traditional knowledge, phytolith analysis, remote sensing, and tree inventories, we describe an area of very large old trees. We show that until now there has been very little to no human impact within these forests and that the current Indigenous footprint is both low and stable. Yet the local communities are not rewarded for their custody of one of the most exceptional forests in the Americas. Results are discussed in the context of sub-optimal carbon finance options. Three novel avenues for including intact forests conservation in the climate change mitigation toolbox are proposed.